A case of mammary-type myofibroblastoma of the inguinal region. (2018) - Ishihara, Atsushi; Yasuda, Takeo; Sakae, Yukari; Sakae, Masayuki; Hamada, Tooru; Tsukazaki, Hideki; Tsukazaki, Takashi; Furumoto, Masaru
Highlights: Mammary-type Myofibroblastoma of the Inguinal Region is very rare. Prognosis of this disease is good after surgical resection. The correct diagnosis and treatment is important. We think that it is useful to share knowledge widely about this disease. Abstract: Introduction: Myofibroblastoma is usually occurred in the breast and extra-mammary disease is rare. Presentation of case: A 38-year-old man was admitted to our hospital for further examination of the left inguinal tumour, present and enlarging for 16 months. The tumor was 50 mm in diameter, well-circumscribed, firm, and painless. Ultrasonogaphy, computed tomography(CT) and magnetic resonance imaging (MRI) could not provide the definitive diagnosis. Surgical exploration confirmed a 50 mm tumour with a clear surface with a thin capsule. Complete excision was achieved. Histopathology confirmed the tumor had oval and spindle shaped fibroblastic cells with rich collagen deposition. It stained positive for ER, CD34, desmin and CD10 but negative for -smooth muscle actin and S-100. A mammary-type myofibroblastoma was diagnosed based on these results. Discussion: An extra-mammary myofibroblastoma is very rare and first reported in 2001. Since then, over 160 cases have been reported. On immunohistochemistry, these lesions are characteristically positive for CD34 and desmin, with variable staining for α-smooth muscle actin. Once the diagnosis is made, regardless of size or location, this tumour behaves in a benign fashion after surgical excision reported so far. Conclusion: This case is rare, but the correct diagnosis and treatment is important for good prognosis.